Inhibitory effect of flavonoids on human glutaminyl cyclase. Issue 10 (15th May 2016) - Li, Manman; Dong, Yao; Yu, Xi; Zou, Yongdong; Zheng, Yizhi; Bu, Xianzhang; Quan, Junmin; He, Zhendan; Wu, Haiqiang
Graphical abstract: Abstract: Glutaminyl cyclase (QC) plays an important role in the pathogenesis of Alzheimer's disease (AD) and can be a potential target for the development of novel anti-AD agents. However, the study of QC inhibitors are still less. Here, phenol-4′ (R1-), C5-OH (R2-) and C7-OH (R3-) modified apigenin derivatives were synthesized as a new class of human QC (hQC) inhibitors. The efficacy investigation of these compounds was performed by spectrophotometric assessment and the structure–activity relationship (SAR) was evaluated. Molecular docking was also carried out to analyze the binding mode of the synthesized flavonoid to the active site of hQC.